2005
DOI: 10.1159/000082896
|View full text |Cite
|
Sign up to set email alerts
|

Female Preponderance in Congenital Adrenal Hyperplasia due to CYP21 Deficiency in England: Implications for Neonatal Screening

Abstract: Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase (CYP21) deficiency causes symptoms ranging from life-threatening neonatal adrenal crises to minimal virilization in adulthood. The relationship between CYP21 genotype and phenotypic markers in a non-screened population of 73 CAH children (44 female, 29 male; 54 white, 19 Asian) treated at the Royal Manchester Children’s Hospital was investigated and ethnic and sex differences assessed. The patients were categorized according to the mutation on the mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
37
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 41 publications
8
37
3
2
Order By: Relevance
“…Notably, we identified fewer adult men than women with classical CAH, which was also reported in England (22). Before newborn screening started in Sweden in 1986, the prevalence of CAH was also higher for girls than for boys (21,23).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Notably, we identified fewer adult men than women with classical CAH, which was also reported in England (22). Before newborn screening started in Sweden in 1986, the prevalence of CAH was also higher for girls than for boys (21,23).…”
Section: Discussionsupporting
confidence: 70%
“…Before newborn screening started in Sweden in 1986, the prevalence of CAH was also higher for girls than for boys (21,23). This is intriguing, since CAH is an autosomal recessive trait with expected equal sex ratio, and may be interpreted as increased neonatal male mortality because of adrenal crises, as male infants are less readily diagnosed and treated than female infants (22). Another explanation may be that some boys with the SV form of CAH remain undiagnosed in adult age (24).…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate associated with a saltloss crisis in CAH is 4 to 10% (8). In our study, no cases of adrenal crisis or death were observed, despite the fact that 37 children presented the salt-wasting form of the disease.…”
contrasting
confidence: 48%
“…Girls with classic CAH have ambiguous genitalia at birth and may be registered and raised improperly as boys (8). We observed in our study that 6% of the children had improper gender identification, hence the importance of early diagnosis and confirmation with karyotype for early correction of the error in establishing the correct gender in affected girls.…”
mentioning
confidence: 57%
See 1 more Smart Citation